Full-genome sequencing and mutation analysis of SARS-CoV-2 isolated from Makassar, South Sulawesi, Indonesia - Massi,Muhammad Nasrum; Abidin,Rufika Shari; Farouk,Abd-ElAziem; Halik,Handayani; Soraya,Gita Vita; Hidayah,Najdah; Sjahril,Rizalinda; Handayani,Irda; Hakim,Mohamad Saifudin; Gazali,Faris Muhammad; Setiawaty,Vivi; Wibawa,Tri (PeerJ, 2022)
Introduction A global surge in SARS-CoV-2 cases is occurring due to the emergence of new disease variants, and requires continuous adjustment of public health measures. This study aims to continuously monitor and mitigate the impact of SARS-CoV-2 through genomic surveillance, to determine the emergence of variants and their impact on public health. Methods Data were collected from 50 full-genome sequences of SARS-CoV-2 isolates from Makassar, South Sulawesi, Indonesia. Mutation and phylogenetic analysis was performed of SARS-CoV-2 from Makassar, South Sulawesi, Indonesia. Results Phylogenetic analysis showed that two samples (4%) were of the B.1.319 lineage, while the others (96%) were of the B.1.466.2 lineage. Mutation analysis of the spike (S) protein region showed that the most common mutation was D614G (found in 100% of the sequenced isolates), followed by N439K (98%) and P681R (76%). Several mutations were also identified in other genomes with a high frequency, including P323L (nsp12), Q57H (ns3-orf3a), and T205I (nucleoprotein). Conclusion Our findings highlight the importance of continuous genomic surveillance to identify new viral mutations and variants with possible impacts on public health.
Keywords: COVID-19; SARS-CoV-2; Whole-genome sequencing; D614G; N439K